Students’ Perception of Their Self-Efficacy by Being a “Hey Peer Educator” in Drug Abuse Prevention - Nurmala, Ira; Salim, Lutfi Agus; Muthmainnah, Muthmainnah; Devi, Yuli Puspita; Harris, Neil; Wiseman, Nicola; Nadia, Asma (Universitas Airlangga, 2024)
Background: Peer education programs provided in schools are one method to help prevent drug abuse; however, the effectiveness of these programs relies, in part, on their delivery to the population in need. Therefore, the effectiveness of the program relies on the self-efficacy of peer educators. The peer education program helps students to practice their skills as peer educators in avoiding drug abuse. Aims: This study aimed to explore the students’ self-efficacy as peer educators after being a peer educator in the peer education program. Methods: In-depth semi-structured interviews were conducted with 45 student peer educators in Middle schools located in Surabaya, Indonesia. Results: Adolescents who acted as student peers perceived and experienced an improvement in their knowledge and ability to help their peers avoid drug abuse. Conclusion: The peer education program is perceived to improve students’ self-efficacy in counseling tasks, to learn analytical skills, and to maintain positive behavior.